Fractionalizing audiences a study on how socio-demographic and psychographic characteristics affect television viewing patterns - Caceres, Khristine Melanie
The study dealt with how socio-demographic and psychographic characteristics affect television viewing patters. It aimed to describe the socio-demographic characteristics of respondents and identify their psychographic traits. It also sought to find out the degree of the respondents' needs and expectations of television. Moreover, the study attempted to find out patterns in television viewing of respondents. It likewise tried to know if there is a relationship between these independent variables and television viewing patterns. A survey was conducted in order to collect data for the study. Respondents for the study include working people and students from government and non-government companies and universities in Quezon City. Of the 110 respondents, 67 were students and 43 were already working. It was found that socio-demographic characteristics such as age, civil status, educational attainment, gender, monthly household income, and occupation were significantly related to television viewing patterns, particularly frequency of viewing, program-type preference, favorite shows, and activities while watching TV. Younger respondents were found to prefer entertainment shows while older respondents preferred watching news and public affairs. It was also found that younger respondents spend more time watching TV. This is also true for students. Older respondents, particularly married females, were more inclined to doing household work while watching TV. However, eating was found to be the activity most preferred by younger respondents, especially the males. Three-fourths of the respondents were found to belong to the Inner-Directed category of psychographics. Within the category, the Experimental typology had the greatest number of respondents. This is characterized by a value for direct experience and participation. The next largest category was found to be Integrated which is characterized by being psychologically mature, self-actualizing and tolerant. Degree of needs and expectations of TV were found to have no relationship to television viewing patterns.